Mutational Analysis of PBRM1 and Significance of PBRM1 Mutation in Anti-PD-1 Immunotherapy of Clear Cell Renal Cell Carcinoma - Aili, Abudureyimujiang; Wen, Jie; Xue, Lixiang; Wang, Junjie (Frontiers in Oncology, 2021)
Renal cell carcinoma is a common solid tumor. PBRM1 is one of the most mutation-prone genes in clear cell renal cell carcinoma (ccRCC) with the occurrence of mutation in 40% of ccRCC patients. Mutations in PBRM1 have been correlated with the efficacy of immunotherapy. However, the mutation types of PBRM1 are not well characterized. The effects of PBRM1 expression levels in the tumor microenvironment are not well studied. The mechanisms and influences of anti-PD-1 immunotherapy in ccRCC tumor microenvironments are not well clarified. In this study, using bioinformatics methods we analyzed the alternation frequency and expression levels of PBRM1 in various tumors. In addition, we experimentally validated its expression levels in ccRCC tissues from human and mouse model. And attempted to clarify the mechanisms of anti-PD-1 immunotherapy in ccRCC with various PBRM1 expression levels. Results showed that deficiency of PBRM1 protein correlated with CD4 T cell reduction in human and mouse ccRCC tissues. We report that anti-PD-1 Immunotherapy can increase the infiltration of T cells in both PBRM1 high and PBRM1 low tumors but with different levels. Our study implies that the reduction of CD4 cells in tumor tissues with low expression of PBRM1 may explain the compromised efficacy of anti-PD-1 immunotherapy in patients with PBRM1 mutated ccRCC. Our study sheds light on the potential of PBRM1 as a therapeutic target in ccRCC.